Earnings Quality in The Retail Industry: The Role of Profit Growth, Capital Structure, and Liquidity in Retail Companies Listed on The Indonesia Stock Exchange (2019–2023) - Mayasari, Yetti; Nengzih, Nengzih (Baileo: Jurnal Sosial Humaniora, 2025)
Earnings quality is a crucial indicator that reflects the reliability of a company’s financial information. Retail companies listed on the Indonesia Stock Exchange (IDX) are expected to present financial reports with high-quality earnings to support accurate decision-making by both internal and external users. This study aims to analyze the impact of profit growth, capital structure, and liquidity on earnings quality in Indonesian retail companies during the 2019–2023 period. This research employs a quantitative approach using purposive sampling, resulting in a sample of 27 retail companies analyzed over five years. The data used are secondary data from corporate financial reports, and the analysis is conducted using multiple linear regression with the assistance of the Statistical Package for the Social Sciences (SPSS) software. The findings indicate that profit growth, capital structure, and liquidity have a significant positive effect on earnings quality. These results confirm that these three factors play a crucial role in generating more reliable earnings information. The novelty of this study lies in the simultaneous examination of the impact of profit growth, capital structure, and liquidity on earnings quality in the retail sector over the 2019–2023 period, which has not been extensively explored holistically in the context of Indonesia’s capital market. This research contributes to the development of social sciences, particularly in accounting and finance theories, specifically regarding the determinants of earnings quality. Additionally, it provides practical recommendations for company management in preparing more transparent and relevant financial reports. For investors, the findings of this study serve as a valuable reference in assessing a company’s financial health, helping to avoid potential investment losses caused by poor earnings quality.